The Influence of Financial Resources on the Implementation of Strategic Plans in Tanzania’s Local Government Authorities: A Survey of Selected LGAs in Morogoro Region - Kaniki, Tabia Hassan; Mwakasangula, Eliza; Shilling, Venance (Journal of Policy and Leadership, 2022)
Financial resources are critical to the successful implementation of strategic plans in Local Government Authorities (LGAs). This study aimed to investigate the influence of financial resources on the implementation of strategic plans in selected LGAs in the Morogoro region of Tanzania. The study was underpinned by the resource-based view theory and pragmatic research philosophy. The study employed a mixed research approach, using an explanatory sequential design with quantitative data exceeding qualitative data. The study sample size was 204, drawn from a target population of 860 employees in all five LGAs. Data were collected using questionnaires and interviews, and qualitative and quantitative data were analysed thematically and through descriptive and inferential statistical analyses respectively. The findings revealed that financial resources had a statistically significant weak positive relationship with the implementation of strategic plans in LGAs and only 8.3 per cent of the variations on the implementation of strategic plans are contributed by all predictors namely financial capacity, adequate budget, timely disbursement, fund utilization). Thus, other factors which were not included in this study contribute about 81.7per cent to the implementation of strategic plans of Tanzania's LGAs in the Morogoro Region. The study concludes that financial resources have a small contribution to the timely execution of strategic plans in LGAs and recommends that enough funds should be allocated and timely disbursed for the effective execution of various strategies.